2002
DOI: 10.1002/1521-4095(20020104)14:1<27::aid-adma27>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Lithium Insertion Properties of Mesoporous Vanadium Oxide

Abstract: The first successful deposition of mesoporous vanadium oxide films and their application as high‐rate cathode materials for lithium batteries are described in this communication. The novel electrochemical deposition process developed for the preparation of these films makes use of non‐ionic surfactant templates. The Figure illustrates the mesoporosity of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 23 publications
4
81
1
1
Order By: Relevance
“…Liu et al synthesized mesoporous vanadium oxide with pore sizes ranging from 3 to 4 nm by electrodepositing from a VOSO 4 solution in the presence of a block polyalkylene oxide polymer (P123). [74] This polymer surfactant plays a key role in the formation of mesoporous structure. The authors specifically investigated the rate performance of the mesoporous vanadium oxide electrode and found that the material delivered a capacity of 125 mA h g À1 at a high rate of 508C, corresponding to a capacitance of 450 F g…”
Section: à2mentioning
confidence: 99%
“…Liu et al synthesized mesoporous vanadium oxide with pore sizes ranging from 3 to 4 nm by electrodepositing from a VOSO 4 solution in the presence of a block polyalkylene oxide polymer (P123). [74] This polymer surfactant plays a key role in the formation of mesoporous structure. The authors specifically investigated the rate performance of the mesoporous vanadium oxide electrode and found that the material delivered a capacity of 125 mA h g À1 at a high rate of 508C, corresponding to a capacitance of 450 F g…”
Section: à2mentioning
confidence: 99%
“…Through the synthesis of electrode materials with nanoscale dimensions, the electrochemical performance of many materials has been greatly improved [17][18][19][20][21] . In recent years, with the rapid development of nanostructure synthesis, electrode materials from mesoporous nanostructures have attracted much attention since it has been shown to provide a significant increase in rechargeable lithium ion battery performance with respect to energy density, life cycle, and speed performance [22][23][24][25][26][27][28][29] . This comes as a direct consequence of a greater specific surface area leading to a concomitant increase in current density.…”
Section: Introductionmentioning
confidence: 99%
“…16 [36][37][38][39][40] and hard/soft templating. [41][42][43][44][45][46] Typically, V 2 O 5 /TiO 2 composites have been prepared for electrochemical use as either amorphous or crystalline thin-films by conventional 25 sol-gel chemistries using the respective metal alkoxide precursors. 21,22,20,[23][24][25][26] …”
Section: Introductionmentioning
confidence: 99%